Digital forensic approaches for metaverse ecosystems - Kim, Donghyun; Oh, Subin; Shon, Taeshik (Forensic Science International: Digital Investigation, 2023)
The accelerating pace of digital transformation has given rise to metaverses that can participate freely in contactless environments. More than just game content, metaverses are driving everyday innovation across industries. However, threats are also prevalent, with crimes such as child sexual exploitation and privacy violations occurring in metaverses that mimic reality, making digital forensics for metaverse threats essential. Nevertheless, technical standards for different types of metaverses have yet to be defined, making investigation difficult. Furthermore, even though metaverses are complex forms that combine multiple hardware devices and software applications, existing studies have either focused on a single component or not analyzed the real-world environment. In this study, we derived a metaverse ecosystem with common components that comprise a metaverse and analyzed the hardware and software used throughout the user's metaverse lifecycle from a digital forensics perspective. In particular, we applied real-case-based scenario to the metaverse environment of the most popular Meta's currently in use to identify various artifacts that can be used across the ecosystem and validate the effectiveness of the process. We also developed a metaverse digital forensics tool for the first time in the current situation where open-source and commercial tools do not support metaverse investigations.
Keywords: Augmented reality; Contact less; Digital transformation; Game contents; Meta; Meta quest; Metaverses; Privacy violation; Technical standards; Virtual reality; Augmented Reality (AR); Digital Forensics; Ecosystem; Meta; Meta Quest; Metaverse; Virtual Reality (VR)